2007
DOI: 10.1124/jpet.107.119446
|View full text |Cite
|
Sign up to set email alerts
|

Induction by Antipsychotics of “Win-Shift” in the Drug Discrimination Paradigm

Abstract: In a two-lever, food-rewarded drug discrimination paradigm, behavior seems to be governed by a win-stay/lose-shift rule; rats continue to press the lever that yields food, and, when not rewarded, they shift responding to the alternative lever. Here, we report on the effects that antipsychotics and further neuropharmacological agents exert in those conditions. At higher doses, antipsychotics disrupt most or all behavioral parameters in this paradigm. However, at lower doses, rats may select the appropriate leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Alterations in dopamine signaling have previously been associated with changes in behavioral flexibility. For example, Colpaert et al (2007) found that systemic dopamine D 2 antagonists increased win-shift behavior after a rewarded trial. Conversely, Halluk and Floresco (2009) found that infusions of the D2 agonist quinpirole directly into the NAcc impaired reversal learning without disrupting initial response learning.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in dopamine signaling have previously been associated with changes in behavioral flexibility. For example, Colpaert et al (2007) found that systemic dopamine D 2 antagonists increased win-shift behavior after a rewarded trial. Conversely, Halluk and Floresco (2009) found that infusions of the D2 agonist quinpirole directly into the NAcc impaired reversal learning without disrupting initial response learning.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the antagonism of either dopamine D 2 receptors, muscarinic receptors, or 5-HT 2A/2C receptors is sufficient to mimic the OLZ-induced interoceptive state. Colpaert et al (2007) used a two-lever, food-rewarded drug discrimination paradigm and found that HAL was more efficacious than OLZ in inducing ‘win-shift’ response pattern, possibly because of its strong D 2 receptor antagonism. As the ‘antipsychotic’ action, as well as the antiavoidance effect is thought to be mediated by antagonism against D 2 receptors (Wadenberg et al , 2001; Seeman, 2006), the compound cue mediated by multiple receptor actions of OLZ is apparently less effective in bestowing an antipsychotic property to CDP than the single cue mediated by D 2 blockade by HAL.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the well-documented salience attenuation effect of antipsychotics (Fouriezos et al , 1978; Berridge and Robinson, 1998; Dickinson et al , 2000; Wise, 2004; Colpaert et al , 2007), the notion that the drug-induced interoceptive state(s) may be involved in the antipsychotic effects is relatively new, although preclinical studies such as those based on drug discrimination and state-dependent learning have long recognized the distinct drug states induced by typical and atypical antipsychotics (Overton, 1979; Goudie et al , 1998; Porter et al , 2000b; Porter et al , 2005). The primary goal of this study was thus to examine this mechanism further, using a novel drug–drug conditioning paradigm in the CAR model.…”
Section: Introductionmentioning
confidence: 99%
“…Here the animals are trained to continue responding on one of two levers as long as that lever yields food reward, and to shift to the other lever when no longer rewarded. With low-doses of haloperidol, animals inexplicably shift to the wrong lever as if they had earned no food with their initial lever-press (Colpaert et al , 2007). That is, haloperidol-treated rats that earned food on their initial lever-press behaved like normal rats that failed to earn food on their initial lever-press.…”
Section: The Hypothesesmentioning
confidence: 99%